2021
DOI: 10.3390/fermentation7040218
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oil Palm Fronds Silage Supplemented with Urea-Calcium Hydroxide on Rumen Fermentation and Nutrient Digestibility of Thai Native-Anglo Nubian Goats

Abstract: This study aimed to examine the combined effects of urea and calcium hydroxide ensiled oil palm fronds on rumen fermentation and digestibility of Thai native-Anglo Nubian goats. A 4 × 4 Latin square design was used to randomly assign four male crossbred goats (Thai native × Anglo Nubian). The dietary treatments were as follows: ensiled oil palm frond with no additives (EOPF as the control), urea 5% (50 g/kg fresh matter) (E-UOPF 5%), calcium hydroxide (Ca(OH)2) 5% (50 g/kg fresh matter) (E-CaOPF 5%), and combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…The increase in plasma glucose with increased CoCP intake revealed the glucogenic capacity of this additive in the current investigation [ 48 ], with a mean glucose amount of 65.79 mg/dL. These results agree with those of Chanjula et al [ 39 ], who observed a mean value of 62.90 mg/dL in goats fed fermented oil palm fronds supplemented with urea-calcium hydroxide. Because the optimal glucose range is 50 to 80 mg/dL [ 46 ], all groups in all samples were within this range.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase in plasma glucose with increased CoCP intake revealed the glucogenic capacity of this additive in the current investigation [ 48 ], with a mean glucose amount of 65.79 mg/dL. These results agree with those of Chanjula et al [ 39 ], who observed a mean value of 62.90 mg/dL in goats fed fermented oil palm fronds supplemented with urea-calcium hydroxide. Because the optimal glucose range is 50 to 80 mg/dL [ 46 ], all groups in all samples were within this range.…”
Section: Discussionsupporting
confidence: 92%
“…The flavonoid component of the plant has been shown to influence rumen microbial metabolism by changing fermentation conditions such as pH and protein breakdown [ 37 ]. High tannin levels in forages were found to impair goat digestibility and feed intake in one study [ 38 ], but another study found that adding tannin in low concentrations to forages can improve goat weight by altering rumen fermentation and reducing internal parasite burdens as well as protecting dietary protein in the rumen [ 39 ]. Saponin and tannin can lower methane and ammonia production in the rumen, resulting in improved animal development and nutrition use [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Srakaew et al [8] reported that slow-fermented starch with alkaline treatment produced fewer short-chain fatty acids (SCFA) and had a higher pH. Likewise, Chanjula et al [10] reported that the pH of the grain treated with CaOH 2 was higher than that of a control group. Deckardt et al [42] reported that the ruminal pH value of barley treated with LA was higher than that of the control group.…”
Section: Ruminal Ph and Ammonia-nitrogen Concentrationsmentioning
confidence: 99%
“…However, the rapid fermentation of high-carbohydrate feeds containing high starch causes a drop in ruminal pH and increases the risk of rumen acidosis [8]. Therefore, more research has been done to find a suitable way of modulating the degradability of starch sources in the rumen and boosting feed efficiency by partially moving starch digestion to the small intestine [9,10]. By increasing resistant starch in the rumen, feed processing techniques, including physical and chemical approaches, can alter starch, reduce rumen-degradable starch, and improve starch flow to the duodenum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation